Implementation of Robotic Process Automation in Public Sector Goods and Services e-Procurement Audit - Ermina Hidayanti; Kamia Achyuniasih Kunrat; Syafrizal Ikram (UIN Sunan Gunung Djati, 2022)
Indonesia has adopted e-Procurement through an electronic procurement system (SPSE) implemented by the Electronic Procurement Service to improve transparency and efficiency in the procurement of goods and services (LPSE). Although the data/information presented in the LPSE is easily accessible, using the data in the LPSE for supervisory or audit functions is still not optimal, despite the fact that procurement of goods and services is the area with the highest corruption cases in Indonesia. The large amount of data in LPSE makes the audit process difficult because there is too much data to consider, especially if the audit process is still manual. As a result, auditors must use information technology to aid audit activities, also known as Computer Assisted Audit Techniques (TABK). In the field of public procurement auditing, the methodology for extracting large amounts of information is also unknown. Robotic Process Automation (RPA), which is thought to have great potential to facilitate audit work, is one of the information technologies that can help with the process of extracting large amounts of data. The author attempts to investigate how the implementation of RPA in the audit of the procurement of goods and services in the public sector that were analyzed descriptively in this study. The study's findings show that process automation can be done well and produce data that can be used in audits.